Effect of Bronchoscopy on Gas Exchange and Respiratory Mechanics in Critically Ill Patients With Atelectasis: An Observational Cohort Study - Smeijsters, Kim M. G.; Bijkerk, Ronald M.; Daniels, Johannes M. A.; van de Ven, Peter M.; Girbes, Armand R. J.; Heunks, Leo M. A.; Spijkstra, Jan Jaap; Tuinman, Pieter R. (Frontiers in Medicine, 2018)
Background: Atelectasis frequently develops in critically ill patients and may result in impaired gas exchange among other complications. The long-term effects of bronchoscopy on gas exchange and the effects on respiratory mechanics are largely unknown. Objective: To evaluate the effect of bronchoscopy on gas exchange and respiratory mechanics in intensive care unit patients with atelectasis. Methods: Retrospective, single-centre cohort study in patients with clinical indication for bronchoscopy because of atelectasis on chest X ray (CXR). Results: In total 101 bronchoscopies were performed in 88 ICU patients. Bronchoscopy improved oxygenation (defined as increase of PaO₂/FiO₂ ratio > 20 mmHg) and ventilation (defined as decrease of > 2 mmHg in partial pressure of CO₂ in arterial blood) in respectively 76% and 59% of procedures for at least 24 hours. Patients with a low baseline value of PaO₂/FiO₂ ratio and high baseline value of PaCO₂, were most likely to benefit from bronchoscopy. In addition, in intubated pressure control ventilated patients, respiratory mechanics improved after bronchoscopy for up to 24 hours. Mild complications were reported in 13% of patients, in particular desaturation between 80-90%. Conclusions: In selected critically ill patients with atelectasis bronchoscopy improves oxygenation, ventilation and respiratory mechanics for at least 24h.